Surface roughness analysis of five-axis flank milling strategies for slanted thin-walled pocketing: aerospace part - Sundi, Syahrul Azwan; Izamshah, Raja; Kasim, Mohd Shahir; Othman, Intan Sharhida; Raffay, Mohamad Razly (2023)
This research was initiated to investigate the effect of surface rough- ness when machining slanted thin-walled pocketing profiles with various flank